A Clinical Study on Hyponatremia in Elderly, Hospitalized Patients (Academia Journal of Medicine, 2019)
Background: Electrolytes abnormalities are very common abnormalities in elderly individuals, among these hyponatramia is very dangerous  and with high mortality hyponatramia is labelled as when serum sodium is less than 135 m.eq/l. It is associated with profound disturbance of  cerebral function. Clinical features of hyponatremia include confusion, lethargy, vomiting convulsions and coma. To most cases of  hypomatremiareflects water imbalance and abnormal water handling not sodium. Rapid rate of development of electrolyte abnormality causes  more severe cerebral symptoms than the levels of Na Aggressive treatment and inappropriate therapy is more harmful than hyponatremia.  Common causes of hyponatremia are dehydration, chronic renal failure, AIDS, Hypothyroidism and infections. Aim: To study the pattern,  clinical features and outcome of patients with hyponatremia. Subjects and Methods: This study in conducted for 1year in 2 rural medical  colleges in Telangana and Andhra Pradesh we have conducted this study on 80 elderly patients. Hospitalized patients. The age group is  between 6.5 and 80 years males were 54 and females were 36. Results: We have examined 80 patients, males were 54 and females were 36.  The age group is between 65 and 80 years. Hyponatremia was observed in 28 patients out of these 28 patients males were 18 and females were  10. The common age group is between 70 and 75 years. Conclusion: Hyponatremia is very common in elderly patients. And it is mostly seen  in pts withCVA CAD, diabetes and sepsis. So when the elderly patients admitted with these coma bid conditions look for the early symptoms  of hyponatremia and serum electrolyte should be tested. Early detection and early managements can prevent the mortality and morbidity is  these patients.
Keywords: Electrolyte abnormalities; Hyponatremia elderly patients; altered sensorium; serum sodium; morbidity